Optimalisasi Potensi Ekspor Produk Gula Jahe Seduh “Berkah” ke Pasar Dunia - Ramadhani, Sekar Ajeng; Waluyo, Retno (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
The increasingly advanced technology and industry today is the key to export activities. Exports can be the driving force of the global economy by contributing more like economic development, country competitiveness, job creation, and innovation. The National Export School focuses on export learning for UMKM, BUMN, and other companies. The mission of the Export School is to create 500,000 new exporters by 2030. The National Export College is working with Merdeka Campus in a Studi Independen Bersertifikat (SIB) program that focuses on the development of UMKM for export to global markets. Ginger sugar product development has significant export potential for local economic growth, and national economic development. The aim of this dedication is to develop ginger sugar products to the international market by increasing consumer demand, expanding the network, and enhancing the brand. The dedication method is implemented using the results of field surveys with business owners.